Familiar strangers and stranger-kings : mobility, diasporas, and the foreign in the eighteenth-century Malay world - Koh, Keng We (2018)
Early modern Malay historiography has been dominated by the history of European trading, colonial empires and local port-polities, often framed along indigenous-versus-foreign lines. Yet, mobility has long been a central feature of this region shaped by commerce, as evidenced by the historical phenomenon of the ‘stranger-king’. This study examines the cultural, political and economic impacts of intra-regional migration and diasporic communities in this region, specifically comparing the interconnected histories of the Chinese, Bugis, Arab, and Minangkabau communities in the seventeenth and eighteenth centuries. Locating this history within that of maritime Asia, this study provides a nuanced understanding of the historical Malay world beyond essentialism and communalism. This article highlights why scholars of the Malay world should take into account the important roles of mobility and ‘strangers’. It concludes that the Malay world was not a timeless or natural construct, but one whose contours and identity were continually shaped by significant diasporic communities and historical encounters.